If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35x + 7 = 36x + 42 Reorder the terms: 7 + 35x = 36x + 42 Reorder the terms: 7 + 35x = 42 + 36x Solving 7 + 35x = 42 + 36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36x' to each side of the equation. 7 + 35x + -36x = 42 + 36x + -36x Combine like terms: 35x + -36x = -1x 7 + -1x = 42 + 36x + -36x Combine like terms: 36x + -36x = 0 7 + -1x = 42 + 0 7 + -1x = 42 Add '-7' to each side of the equation. 7 + -7 + -1x = 42 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 42 + -7 -1x = 42 + -7 Combine like terms: 42 + -7 = 35 -1x = 35 Divide each side by '-1'. x = -35 Simplifying x = -35
| 23+x=26 | | S+2=9 | | x^3-3x=9.8 | | 8*w*2w= | | 71=-9+8x | | 19+2x=79 | | 7c*3e= | | (2*11)-(2*x)= | | (-5)3/(-5)3= | | 16-y=3y-8 | | 10=2p+2 | | 56-7x= | | Z-15=31 | | 2.8(3-2x)+3.2x=6.3-2(x-1.4) | | (8r-1)(5+2r)=(4r+5) | | x+y+39=36 | | (8r-1)(5+2r)=(4r+5)2 | | x/10=10/20 | | 1.06(53+x)=83+x | | 99-11x= | | 15x-3=5x-43 | | 1.7x+-1.62x=0.4x-0.32+8 | | 2k-5=10 | | 3x^2+14x-27=0 | | 14m^2-23m+8=0 | | x(-2a)=3a(x-2a) | | T-7b=3 | | 343/5832 | | X+12=y | | M+9=n | | t^2+2t-5=0 | | 2xy+8x-3y-4=0 |